Ethnographies of home and mobility : shifting roofs - Miranda Nieto, Alejandro; Massa, Aurora; Bonfanti, Sara (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book lays out a framework for understanding connections between home and mobility, and situates this within a multidisciplinary field of social research. The authors show how the idea of home offers a privileged entry point into forced migration, diversity and inequality. Using original fieldwork, they adopt an encompassing lens on labour, family and refugee flows, with cases of migrants from Latin America, Africa and the Indian subcontinent. With the book structured around these key topics, the authors look at how practices of home and mobility emerge along with emotions and manifold social processes. In doing so, their scope shifts from the household to streets, neighbourhoods, cities and even nations. Yet, the meaning of 'home' as a lived experience goes beyond place; the authors analyse literature on migration and mobility to reveal how the past and future are equally projected into imaginings of home.
Foreword: Mainstreaming the study of home and migration Introduction: Unlocking doors 1. Scales 2. (Im)materiality 3. Mobility and immobility 4. Temporalities 5. Diversities 6. Inequalities Conclusion: Dwelling between mobility and stasis Afterword Index.
OCLC-licensed vendor bibliographic record.
Keywords: Emigration and immigration -- Social aspects; Home; SOCIAL SCIENCE / Anthropology / General